Clinical Feasibility of Ultrafast Contrast-Enhanced T1-Weighted 3D-EPI for Evaluating Intracranial Enhancing Lesions in Oncology Patients: Comparison with Standard 3D MPRAGE Sequence - Ryu, K.H.; Baek, H.J.; Skare, S.; Cho, E.; Nam, I.C.; Kim, T.H.; Sprenger, T. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Contrast-enhanced 3D T1WI is a preferred sequence for brain tumor imaging despite the long scan time. This study investigated the clinical feasibility of ultrafast contrast-enhanced T1WI by 3D echo-planar imaging compared with a standard contrast-enhanced 3D MPRAGE sequence for evaluating intracranial enhancing lesions in oncology patients.MATERIALS AND METHODS: Sixty-one patients in oncology underwent brain MR imaging including both contrast-enhanced T1WI, 3D-EPI and 3D MPRAGE, in a single examination session for evaluating intracranial tumors. Two neuroradiologists evaluated image quality, lesion conspicuity, diagnostic confidence, number and size of the lesions, and contrast-to-noise ratio measurements from the 2 different sequences.RESULTS: Ultrafast 3D-EPI T1WI did not reveal significant differences in diagnostic confidence, contrast-to-noise ratiolesion/parenchyma, and the number of enhancing lesions compared with MPRAGE (P > .05). However, ultrafast 3D-EPI T1WI revealed inferior image quality, inferior anatomic delineation and greater susceptibility artifacts with fewer motion artifacts than images obtained with MPRAGE. The mean contrast-to-noise ratioWM/GM and visual conspicuity of the lesion on ultrafast 3D-EPI T1WI were lower than those of MPRAGE (P < .001).CONCLUSIONS: Ultrafast 3D-EPI T1WI showed comparable diagnostic performance with sufficient image quality and a 7-fold reduction in scan time for evaluating intracranial enhancing lesions compared with standard MPRAGE, even though it was limited by an inferior image quality and frequent susceptibility artifacts. Therefore, we believe that ultrafast 3D-EPI T1WI may be a viable option in oncology patients prone to movement during imaging studies.CEcontrast-enhancedCNRcontrast-to-noise ratioICCintraclass correlation coefficientSPACEsampling perfection with application-optimized contrasts by using different flip angle evolutions